A new species of Anthozela from Vietnam, with a list of species in the genus (Lepidoptera: Tortricidae: Olethreutinae: Enarmoniini) - Heppner, John B.; Bae, Yang-Seop (Zootaxa, 2018)
The genus Anthozela Meyrick (1913) is reported for the first time from Vietnam, represented by the new species Anthozela cypriflammella Heppner & Bae, n. sp. A list of the species of Anthozela and related genera is provided.